The Demand for Rail Freight Tranport in Europe - António Fidalgo Couto (2009)
This paper provides the estimation of an aggregate freight railway demand function to analyze effects arising from a change of a variety of economic, technological and demographic characteristics. Thus, the paper presents estimates of demand elasticities with respect to price, income, quality of service and a range of exogenous characteristics. The results reveal that freight transport exhibit a slight increase of traffic density but significant returns to network length. In contrast to previous studies, this study reveals that the aggregate own and cross price elasticities of the rail freight demand are quite inelastic. Demographic/environmental characteristic elasticities confirm expectations that rail freight transport is particularly competitive for long run movements between major city agglomerations. Moreover, the elasticities related to the variation in the supply of alternative transport modes indicate that there are complementarities between sea and inland waterway modes and the rail mode. With respect to road transport, rail demand response is considered to be as sensitive to price as to supply. In global terms, it is clear that the railway transport mode gains greater competitiveness from road transport rather than from air and maritime transport modes.